2020
DOI: 10.1089/ten.teb.2019.0349
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Stem Cell-Derived Extracellular Matrices: Decellularization, Characterization, and Biological Function

Abstract: Stem cells, including mesenchymal stem cells and pluripotent stem cells, have attracted considerable attention in tissue engineering and regenerative medicine primarily because of their unique ability in self-renewal and multilineage differentiation. However, stem cells also have important secretory functions that form a specialized in vivo microenvironment and direct tissue development and regeneration. Extracellular matrices (ECMs) derived from stem cells retain the functional properties of their native envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 194 publications
2
47
0
Order By: Relevance
“…shown that MSCs cultured on these surfaces exhibited improved proliferation capacity, maintenance of phenotype, and increased differentiation potential (Shakouri-Motlagh et al, 2017;Sart et al, 2020). However, the mechanisms of these effects remained to be poor understood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…shown that MSCs cultured on these surfaces exhibited improved proliferation capacity, maintenance of phenotype, and increased differentiation potential (Shakouri-Motlagh et al, 2017;Sart et al, 2020). However, the mechanisms of these effects remained to be poor understood.…”
Section: Discussionmentioning
confidence: 99%
“…The development and application of dECM matrices, prepared both by decellularization of tissues or whole organs and cell-based constructs, has grown rapidly in the fields of cell biology, tissue engineering and regenerative medicine in recent years ( Hoshiba, 2017 ; Rana et al, 2017 ; Shakouri-Motlagh et al, 2017 ; Parmaksiz et al, 2020 ; Riis et al, 2020 ; Sart et al, 2020 ). The source of cells producing ECM is of great importance for realizing its functional role ( Cramer and Badylak, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations